Inotuzumab Ozogamicin and Low-Intensity Chemotherapy in Older Patients With Newly Diagnosed CD22+ Philadelphia Chromosome-Negative B-Cell Precursor Acute Lymphoblastic Leukemia - Chevallier, Patrice; Leguay, Thibaut; Delord, Marc; Salek, Cyril; Kim, Rathana; Huguet, Françoise; Hicheri, Yosr; Wartiovaara-Kautto, Ulla; Raffoux, Emmanuel; Cluzeau, Thomas; Balsat, Marie; Roth-Guepin, Gabrielle; et al. (Journal of clinical oncology, 2024)
PURPOSE: The use of inotuzumab ozogamicin (InO), a conjugated anti-CD22 monoclonal antibody, is becoming a promising frontline treatment for older patients with ALL. PATIENTS AND METHODS: EWALL-INO is an open-label prospective multicenter phase II trial (ClinicalTrials.gov identifier: NCT03249870). Patients age 55 years and older with newly diagnosed CD22+ Philadelphia chromosome-negative (Ph-) B-cell precursor (BCP) ALL were eligible. After a prephase, a first induction consisting of vincristine, dexamethasone, and three injections of InO (0.8 mg/m2 day 1, 0.5 mg/m2 day 8/day 15) was followed by a second induction combining cyclophosphamide, dexamethasone, and two injections of InO (0.5 mg/m2 day 1/day 8). Responders received up to six cycles of chemotherapy consolidation and 18-month chemotherapy maintenance. Allotransplant was allowed after three consolidations. The primary end point was 1-year overall survival (OS). RESULTS: Between December 2017 and March 2022, 131 patients (median age 68 years) were included. Three patients died during induction 1 (n = 130), two from multiple organ failure and one from hemorrhage, and none during induction 2 (n = 120). After induction 2, 90% of the patients achieved complete remission (CR) or CR with incomplete platelet recovery (CRp) and 80% had measurable residual disease (MRD2) <10-4. Among responders (n = 119), 47 relapsed and 14 died in CR/CRp. One-year OS, relapse-free survival (RFS), and cumulative incidence of relapse (CIR) rates were 73.2%, 66%, and 25%, respectively. High-risk cytogenetics and lower CD22 expression (<70%) were associated with worse OS, while both high-risk cytogenetics and MRD2 ≥10-4 were associated with lower RFS and higher CIR. The 10 allotransplanted patients had very favorable outcomes (90% 2-year OS/RFS and no relapse). Only one nonfatal sinusoidal obstructive syndrome was documented during the study. CONCLUSION: Our results support InO's use in first-line regimens for older patients with CD22+ Ph- BCP-ALL.
Keywords: dexamethason; Sialic Acid Binding Ig-like Lectin 2; Vincristine; Humans; lidé středního věku; Inotuzumab Ozogamicin; Female; Aged; protokoly protinádorové kombinované chemoterapie; inotuzumab ozogamicin; senioři; lidé; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; ženské pohlaví; Male; Middle Aged; vinkristin; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Philadelphia Chromosome; Cyclophosphamide; senioři nad 80 let; antigeny CD22; mužské pohlaví; prospektivní studie; pre-B-buněčná leukemie; cyklofosfamid; filadelfský chromozom; Prospective Studies